2018
DOI: 10.3390/molecules23123375
|View full text |Cite
|
Sign up to set email alerts
|

MgONPs Can Boost Plant Growth: Evidence from Increased Seedling Growth, Morpho-Physiological Activities, and Mg Uptake in Tobacco (Nicotiana tabacum L.)

Abstract: In this study, we documented the impact of magnesium oxide nanoparticles (MgONPs) on the various morpho-physiological changes by root irrigation in tobacco plants in the matrix media, as well as the uptake and accumulation of the NPs over a range of concentrations (50–250 μg/mL). Our results showed that the seed germination rate was not affected following exposure to MgONPs for 5 days. Enhanced plant growth together with increased peroxidase activity (39.63 U mg−1 protein in the 250 μg/mL MgONPs treatment, 36.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Fittingly, low soil pH is conducive for the appropriate dissolution of metal ions, even though nanoparticles aggregate (Bian et al, 2011). It is believed that nMgO could potentially be applied as nanofertilizers for supplemental nutrients in agriculture without any toxicity to plants (Cai et al, 2018b). Moreover, recent studies have shown that, as a result of their unique properties, nanoparticles may influence lettuce (Lactuca sativa) metabolic activities, improving and mobilizing phosphorus availability and uptake in the rhizosphere (Zahra et al, 2015;Saharan et al, 2016).…”
Section: Efficiently Managing Soilborne Fungal Diseasesmentioning
confidence: 99%
“…Fittingly, low soil pH is conducive for the appropriate dissolution of metal ions, even though nanoparticles aggregate (Bian et al, 2011). It is believed that nMgO could potentially be applied as nanofertilizers for supplemental nutrients in agriculture without any toxicity to plants (Cai et al, 2018b). Moreover, recent studies have shown that, as a result of their unique properties, nanoparticles may influence lettuce (Lactuca sativa) metabolic activities, improving and mobilizing phosphorus availability and uptake in the rhizosphere (Zahra et al, 2015;Saharan et al, 2016).…”
Section: Efficiently Managing Soilborne Fungal Diseasesmentioning
confidence: 99%
“…It activates enzymes and is an essential element in the photosynthesis process. Moreover, it is a very important nutrient for human health [24,25]. S. Shinde et al synthesized magnesium hydroxide (Mg(OH) 2 ) nanoparticles and investigated their influence on the germination of Zea mays [26].…”
Section: Introductionmentioning
confidence: 99%
“…Out of all treatments, only MgONPs resulted in a notable increase in total chlorophyll in pepper plants at 150 and 200 mg/L. Similarly, Cai et al (2018a), found out that MgONPs increased the chlorophyll a and b contents in tobacco plants remarkably from 0.21 and 0.12 μg/g to 1.21 and 0.67 μg/g, respectively, after 30 days of treatment. Moreover, Raliya et al (2014), demonstrated that biosynthesized MgONPs improved chlorophyll photosynthetic pigment with a value of 76.1% in cluster beans.…”
Section: Discussionmentioning
confidence: 72%